Regulatory scientific advice on non-inferiority drug trials. - Grace Wangge (Public Library of Science (PLoS), 2013)
The active-controlled trial with a non-inferiority design has gained popularity in recent years. However, non-inferiority trials present some methodological challenges, especially in determining the non-inferiority margin. Regulatory guidelines provide some general statements on how a non-inferiority trial should be conducted. Moreover, in a scientific advice procedure, regulators give companies the opportunity to discuss critical trial issues prior to the start of the trial. The aim of this study was to identify potential issues that may benefit from more explicit guidance by regulators. To achieve this, we collected and analyzed questions about non-inferiority trials posed by applicants for scientific advice in Europe in 2008 and 2009, as well as the responses given by the European Medicines Agency (EMA). In our analysis we included 156 final letters of advice from 2008 and 2009, addressed to 94 different applicants (manufacturers). Our analysis yielded two major findings: (1) applicants frequently asked questions 'whether' and 'how' to conduct a non-inferiority trial, 26% and 74%, respectively, and (2) the EMA regulators seem mainly concerned about the choice of the non-inferiority margin in non-inferiority trials (36% of total regulatory answers). In 40% of the answers, the EMA recommended using a stricter margin, and in 10% of the answers regarding non-inferiority margins, the EMA questioned the justification of the proposed non-inferiority margin. We conclude that there are still difficulties in selecting the appropriate methodology for non-inferiority trials. Straightforward and harmonized guidance regarding non-inferiority trials is required, for example on whether it is necessary to conduct such a trial and how the non-inferiority margin is determined. It is unlikely that regulatory guidelines can cover all therapeutic areas; therefore, in some cases regulatory scientific advice may be used as an opportunity for tailored advice.